THEORETICAL ISSUES OF LONG-TERM ASSETS (Marketing Journal, 2025)
This article analyzes theoretical issues related to long -term assets in the field of accounting. It reviews various approaches and regulatory documents concerning such assets, which are presented in the form of shares, bonuses, or resources acquired by enterprises for long -term use. Moreover, long -term financial investments and assets recognized as investment property are considered among the most effective directions for future capital allocation. Therefore, reconsidering the classification and characteris tics of long -term assets is of particular importance.
Keywords: long-term assets; principles; development trends; costs; royalties; rights; uncertainty; practice; relationships; investment; investment property